Antioxidant capacity, radical scavenging ability, total phenols and flavonoids in three types of betelvine (Piper betle L.) - G A Geetha, K S Shivashankara, T K Roy, (Journal of Spices and Aromatic Crops, 2012)
Betelvine (Piper betle L.) leaves from female (Bengaluru local), male (Madras type) and meeta paan (sweet type) were analysed for antioxidant capacity (FRAP) and radical scavenging ability (DPPH) using acidic methanol extracts. FRAP and DPPH values were higher in the leaves of Bengaluru local followed by Madras type and were lowest in sweet type of betelvine. However, chlorophyll was higher in female and sweet betelvine when compared to Madras type. Bengaluru local also recorded higher total phenols and flavonoids followed by Madras type and sweet betelvine recorded lowest phenols and flavonoids. Higher antioxidant and radical scavenging capacities of female and male types was mainly due to the higher phenols and flavonoids and not due to total chlorophyll content. The study indicated that the total phenol content of betelvine is comparable with that of tea powder.